Hukum Kasih menurut Paulus dalam Rom 12:9-21 dan Gemanya dalam Diskursus Kosmopolitanisme - Petrus Nandi; Arsensius Royman Baruk; Yanuarius Asan Berek; Patrisius Dewa Panggo; Adolfo Martins de Deus; Stanislaus Erson; Siprianus Soleman Senda (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
The background of this article is the awareness of the importance of the law of love as a special language of religion (Christianity) for universal human civilization. The author realizes that conventional legal languages, both civil and moral, are not enough to provide a solid normative basis for the transnational cohesion project fought for in cosmopolitanism. The Christian law of love written by Paul in the text of Romans 12:9-21 can be an alternative answer amidst the flow of cosmopolitanism's search for a religious legal language in supporting world peace. The method used is library research with a comparative descriptive analysis approach. On the one hand, there is a description of the law of love from Paul's perspective, and on the other hand, there is a comparison of ideas with cosmopolitanism that is developing today. So this article aims to describe the law of love according to Paul in the text of Romans 12:9-21 and its theoretical and practical relevance in the discourse of cosmopolitanism. The expected result is a new perspective on cosmopolitanism based on the law of love formulated by Paul in the text of Romans 12:9-13.